Efikasi Diri Guru BK dalam Melaksanakan Konseling Kelompok dengan Pendekatan Realitas di SMP Indralaya Kabupaten Ogan Ilir - Lestari, Melisa (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2022)
This study aims to determine the self-efficacy of Counseling teachers in implementing group counseling with a reality approach at Indralaya Middle School, Ogan Ilir Regency. This research method uses descriptive quantitative, the subject of this research is 20BK teachers, namely the MGBK SMP/MTS group in Indralaya, Ogan Ilir Regency who participated in training in community service activities carried out by Guidance and Counseling Study Program Lecturers. The data was taken using a self-efficacy questionnaire distributed via google form. Data analysis using percentages. The results of this study indicate that in general, self-efficacy in implementing group counseling with a reality approach to BK teachers is in the moderate category, which tends to be high (60%). While the high category (25%), low category (15%). Meanwhile, the results of the research specifically on the dimensions of selfefficacy of BK teachers on the difficulty level dimension (level) 60% with the moderate category tending to be high, 20% in the high category, 20% then on the strength dimension, 25% with the high category, 60% with the high category. moderate tend to be high, 15% with low category. And on the generality dimension, 20% is in the high category, 55% in the medium category tends to be high, and 25% in the low category.